Gendered genetics: How reading about the genetic basis of sex differences in biology textbooks could affect beliefs associated with science gender disparities. Issue 4 (18th February 2019) - Donovan, Brian M.; Stuhlsatz, Molly A. M.; Edelson, Daniel C.; Buck Bracey, Zoë E.
Abstract: The belief that men and women differ in science ability because of genetics contributes to gender disparities in science, technology, engineering, and math (STEM) in complex ways. In this field experiment, we explored how the content of the genetics curriculum affected beliefs about science ability through its impact on a social–cognitive bias known as neurogenetic essentialism. Students ( n  = 460, 8th–10th grade) were randomized to read a genetics text that (a) explained plant sex differences, (b) explained human sex differences, or (c) refuted neurogenetic essentialism. After reading, students in the two genetics of sex conditions had significantly greater belief in neurogenetic essentialism and the innate basis of science ability compared with students who read the text that refuted neurogenetic essentialism. Structural equation modeling (SEM) of the experimental data demonstrated that the effect of the readings on the belief that science ability is innate was mediated by neurogenetic essentialism and this indirect effect was significant for girls but not boys. In turn, the belief that science ability is innate predicted lower future interest in STEM for girls, but not for boys. These findings suggest that learning about human genetic difference is not a socially neutral endeavor. Implications for mitigating gender disparities in STEM are discussed.